Disproportionate dyspnea in a patient with pneumonia - Vishnu Sharma Moleyar; Alka C Bhat; Y Madhusudan; D S Harsha (Medical Journal of Dr. D.Y. Patil University, 2017)
In severe pneumonia, dyspnea occurs due to hypoxia. Usually, in pneumonia, dyspnea is proportional to the extent of lung parenchymal lesion. When a patient with pneumonia presents with disproportionate dyspnea, other causes for dyspnea should be evaluated. Here, we present a 48-year-old female with pneumonia, found to have disproportionate dyspnea. Her hypoxia did not improve despite adequate antibiotic and oxygen therapy. On further enquiry, she admitted taking dapsone for leprosy. She had saturation gap diagnostic of methemoglobinemia. Diagnosis was confirmed by estimation of methemoglobin level in blood. She was treated with intravenous methylene blue and recovered. When a patient has disproportionate dyspnea, methemoglobinemia should be considered as a differential diagnosis.